Positive Psychology Broadens Readers’ Attentional Scope During L2 Reading: Evidence From Eye Movements - Leung, Chi Yui; Mikami, Hitoshi; Yoshikawa, Lisa (Frontiers in Psychology, 2019)
While positive psychology has drawn increasing interests among researchers in the SLA literature recently, little is known with respect to the relationship between positive psychology and mental processes during L2 reading. To bridge the gap, the present study investigated whether and how positive psychology (self-efficacy) influences word reading strategies during L2 sentence reading. Based on previous studies, eye-movement patterns with first-fixation locations closer to the beginning of a word can be characterized as an attempt to process the word with a local strategy, whereas first-fixation locations farther away from the beginning and closer to the center of a word can be considered as an attempt to use a global strategy. Eye movements of a group of Japanese learners of English (N = 59) were monitored, and L2 reading self-efficacy was used to assess the participants’ positive belief towards their L2 reading skills. Based on B. L. Fredrickson’s (1998) broaden-and-build theory, we predicted an effect of L2 reading self-efficacy on participants’ first-fixation locations. Results from mixed-effects regression showed that while reading strategies depended in part on other factors such as L2 reading proficiency and word properties, L2 self-efficacy influenced reading strategy. The present data suggest that while more self-efficacious L2 readers prefer a more efficient global strategy, attempting to read the word as a whole word, less self-efficacious L2 readers tend to employ a local strategy, focusing more on sublexical information. These findings lend support to the broaden-and-build theory in the context of L2 processing. The present study has implications for how positive psychology works along with L2 proficiency in the development of strategic selection during reading.